Konsep Pengendalian Mutu Pada Pembuatan Permen Jelly Nenas (Ananas Comosus L.) - Nur Amaliah; Farida Farida (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2019)
In the process of processing jelly candy pineapple requires supervision related to food safety and quality assurance. food quality control is one way to get safe and healthy products according to panelists' requests. The aim is to determine the effect of gelling agent on jelly pineapple candy products, to determine the process of making jelly pineapple candy by applying the concept of quality control, and knowing the level of product preference and quality from organoleptic testing. The method used is quantitative qualitative descriptive where the results of the analysis obtained will be described. The results obtained are gelatin is the best gelling agent in making pineapple jelly candy products. Control control point in the manufacture of jelly pineapple candy is the selection of raw materials, standard weighing material, processing temperature, and drying. The results of chemical analysis of pineapple jelly candy for water content of 15.30%, ash content 0.89%, protein content 1.49%, carbohydrate 82.03%, crude fat 0.79%, fiber 1.25%, and vit C 13.10 mg / 100 g sample. Microbiological analysis, there are 1.3x10-3 colonies / g and E.coli bacteria analysis is <3 APM / g. The results of organoleptic analysis from the level of preference of panelists in pineapple candy are rather like the color, aroma, taste, while liking the texture. The hedonic quality test for pineapple candy is rather not bright yellow in color, chewy and elastic in texture, slightly pineapple-flavored, and sweet. The results of chemical and microbiological analysis are in accordance with SNI for jelly candy, while organoleptic tests require modification to get the best product according to consumer demand.